Change of HBsAg Screening and Seropositivity in Pregnant Women By the Years - Gökhan TOSUN (Flora Infeksiyon Hastalıkları ve Klinik Mikrobiyoloji Dergisi, 2019)
Introduction: Routine examination of HBsAg during pregnancy is vital in the management of pregnancy complications and protection of the newborn. After the hepatitis B vaccination program since 1998 and publication of the prenatal care guidelines in 2014, HBsAg screening is recommended for all pregnant women. The aim of our study is to evaluate HBsAg screening status and results in pregnant women in second stage hospital with high pregnancy rate, which may be indicative of Aegean region of Turkey.